Maximal methane potential of different animal manures collected in northwest region of China - Fen, Chen; Gao, Yu; Wei, Li; Fenwu, Liu; Wuping, Zhang; Yushan, Bu; Xiaomei, Li (International Journal of Agricultural and Biological Engineering, 2017)
Maximum methane potential (B0) is an important parameter used in assessing suitability of a substrate for biogas production. This study examined maximum methane potential of different manures generated from three major Chinese livestock, namely chicken, hog and cattle, and evaluated the important factors that affect the maximum methane potential of a substrate. The livestock manures collected from the local farms were incubated under a thermophilic anaerobic condition (55°C). The results showed that the maximum methane potential (B0) of cattle, hog and chicken manures were 292.0 mL/g VS, 272.0 mL/g VS and 266.4 mL/g VS, respectively. The B0 value decreases with increasing contents of crude protein and crude fat, while increases with increasing the contents of carbohydrates and crude fiber in manures. The content of NH4+-N in chicken manure was significantly higher during the digestion period, reached as high as 1962.5 mg/L by the end of incubation period. Heavy metals of Cu and Zn in the manure also affect the B0. Empirical relationships that describe the B0 decrease in response to increase of Zn and Cu contents in manure were developed and used as a simple tool to assess the effects of these metals on the B0. It was concluded that the protein, Cu and Zn contents of manure are most important chemical compositions that negatively affect maximum methane potential. Based on the three experimental manures, the maximum methane potential was limited by either ammonium content or Cu and Zn content in the manure. For a commercial biogas production facility using these manures as main feedstock, one should consider to add co-substrate or co-substrates to reduce concentration of these chemicals to maximize biogas production.Keywords: anaerobic digestion, manure compositions, biomethane potential, volatile solid degradationDOI: 10.3965/j.ijabe.20171001.2469Citation: Chen F, Yu G, Li W, Liu F W, Zhang W P, Bu Y S, et al. Maximal methane potential of different animal manures collected in northwest region of China. Int J Agric & Biol Eng, 2017; 10(1): 202-208.